2019
DOI: 10.1371/journal.pone.0223250
|View full text |Cite
|
Sign up to set email alerts
|

Unweaving tangled mortality and antibiotic consumption data to detect disease outbreaks – Peaks, growths, and foresight in swine production

Abstract: As our capacity to collect and store health data is increasing, a new challenge of transforming data into meaningful information for disease monitoring and surveillance has arisen. The aim of this study was to explore the potential of using livestock mortality and antibiotic consumption data as a proxy for detecting disease outbreaks at herd level. Changes in the monthly records of mortality and antibiotic consumption were monitored in Danish swine herds that became positive for porcine reproductive and respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…A univariate dynamic linear model (DLM) with a local linear trend component, as described in detail by West and Harrison (11) and applied in previous studies (12)(13)(14)(15), was used to model data at the herd level. A previous study showed that Bayesian forecasting methods adapt faster to changes in the data, compared to the deterministic Holt's linear trend methods for monitoring trends of time-series (14).…”
Section: Modeling and Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A univariate dynamic linear model (DLM) with a local linear trend component, as described in detail by West and Harrison (11) and applied in previous studies (12)(13)(14)(15), was used to model data at the herd level. A previous study showed that Bayesian forecasting methods adapt faster to changes in the data, compared to the deterministic Holt's linear trend methods for monitoring trends of time-series (14).…”
Section: Modeling and Parameterizationmentioning
confidence: 99%
“…where m t is the filtered mean of the antimicrobial consumption at time t and T t is the local linear trend at time t. This local linear trend was incorporated into the model to allow the system to adapt to a possible positive or negative growth in antimicrobial consumption as follows the example given in previous studies (13)(14)(15). A detailed description of the full model, as well as the R code, can be found in the literature (15).…”
Section: Modeling and Parameterizationmentioning
confidence: 99%
“…Previous research adopted autoregressive integrated moving average models [8,46] or the Holt-Winters forecasting method to deal with temporal correlation. In cases where temporal correlation could be ignored or removed, control charts such as Shewhart charts, exponentially weighted moving average charts, and cumulative sum charts were common options of aberration detection for SyS systems [5,12,[47][48][49][50][51]. However, these methods were less suitable for our system since we could not assume the constancy of the analyzed time series.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality can be considered as one of the most important animal health indicators, making it particularly important to record this parameter consistently Fattening pigs Bursa alterations, lameness, dirty animals, runts, and tail, flank and ear biting (Wadepohl et al, 2020) in a database (Lopes Antunes et al, 2017). Monitoring of mortality rates in combination with antibiotic usage data was found to have a predictive value in forecasting infectious disease on farms (Lopes Antunes et al, 2019). So-called 'iceberg indicators' might be helpful to assess welfare, health, management and productivity on farms to evaluate and improve housing and management systems.…”
Section: Potential Indicators For Assessment Of Housing Systemsmentioning
confidence: 99%